2020
DOI: 10.1111/jcmm.15026
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin protects against diabetic encephalopathy via SIRT1/NLRP3 pathway in db/db mice

Abstract: Epidemiological studies have found that diabetes and cognitive dysfunction are closely related. Quercetin has been certified with the effect on improving diabetes mellitus (DM) and cognitive impairment. However, the effect and related mechanism of quercetin on diabetic encephalopathy (DE) are still ambiguous. In this study, we used the db/db mice (diabetic model) to discover whether quercetin could improve DE through the Sirtuin1/NLRP3 (NOD‐, LRR‐ and pyrin domain‐containing 3) pathway. Behavioural results (Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 73 publications
(155 reference statements)
4
31
0
1
Order By: Relevance
“…Interestingly, the quercetin was able to increase the expression of SIRT1 and decrease the expression of NLRP3 inflammasome components such as NLRP3 and adapter protein ASC and activated caspase-1. The quercetin also decreased the expression of proinflammatory cytokines, such as IL-1β and IL-18 [31]. The findings of this study are extremely important because SIRT1 is a pivotal factor.…”
Section: Effect Of Quercetin On Sirt1 As Anti-inflammatory Factor and Nlrp3 Inflammasome Inhibitorsupporting
confidence: 52%
“…Interestingly, the quercetin was able to increase the expression of SIRT1 and decrease the expression of NLRP3 inflammasome components such as NLRP3 and adapter protein ASC and activated caspase-1. The quercetin also decreased the expression of proinflammatory cytokines, such as IL-1β and IL-18 [31]. The findings of this study are extremely important because SIRT1 is a pivotal factor.…”
Section: Effect Of Quercetin On Sirt1 As Anti-inflammatory Factor and Nlrp3 Inflammasome Inhibitorsupporting
confidence: 52%
“…It was also found that the activation of the NF-κB signaling pathway was not significantly influenced by the silencing of of NLRP3 in the TNF-α-induced inflammatory microenvironment. Studies have revealed that Quer can attenuate diabetic encephalopathy and protect against isoniazid-induced hepatotoxicity by suppressing the NLRP3 pathway ( 30 , 48 ). Likewise, the present study determined that Quer downregulated the expression of NLRP3 inflammasome-associated proteins and genes treated in the hPDLSCs stimulated with TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, the phenolic compound quercetin can inhibit NFκB and MMP9 activity [ 108 ]. It can also significantly decrease NLRP3 inflammasome formation [ 133 , 134 , 135 , 136 ]. Thus, quercetin from food and as a supplement may to protect BBB integrity and prevent the activation of DAM in ApoE4 carriers.…”
Section: Precision Nutrition Considerationsmentioning
confidence: 99%